The Impact of Al-Albānī’s Revolutionary Approach to Hadith on Islamic Militancy in Indonesia - Musyafiq, Ahmad (Al-Jami'ah: Journal of Islamic Studies, 2023)
The rise of Islamic militancy among Indonesian Salafis closely relates to their literal understanding of the hadith as the resource of their religious doctrines, with Muḥammad Nāṣiruddīn al-Albānī (1914-1999) as the most referenced figure. This article analyses how the thought of al-Albānī on hadith impacted Islamic militancy development in Indonesia. The writer argues that al-Albānī’s pupils support the rapid spread of his thinking on the hadith with their book publishers, organisations, and Salafi pesantrens. Meanwhile, the impact of al-Albānī’s thoughts on the Salafi movement in Indonesia appears in three notions: the domination of the textual understanding of the hadiths, the growth of al-Lā Madhhabiyyah (not relying on any classical madhab of fiqh), and the taṣfiyah and tarbiyah program. According to al-Albānī, the program of taṣfiyah and tarbiyah is the only way to build an Islamic society, which is a condition for the establishment of the Islamic Sharia and the Islamic State (Daulah Islāmiyyah).[Munculnya gerakan Islam militan di Indonesia tidak bisa dilepaskan dari model pemahaman hadis yang literal dengan tokoh rujukan Muḥammad Nāṣiruddīn al-Albānī (1914-1999). Artikel ini menganalisis pemikiran al-Albānī tentang hadis, yang berdampak pada militansi Islam di Indonesia. Temuan dari tulisan ini  adalah: 1) massifnya penyebaran pemikiran al-Albānī didukung oleh para murid al-Albānī yang mengembangkan penerbit buku, ormas, dan pesantren salafi; 2) dampak pemikiran al-Albānī terhadap pemikiran Salafi di Indonesia dapat dilihat pada tiga hal: dominasi pemahaman tekstual; tumbuhnya gerakan al-Lā Madhhabiyyah (paham untuk tidak bertumpu pada mazhab fikih klasik tertentu); dan program taṣfiyah dan tarbiyah. Menurut al-Albānī, tanpa taṣfiyah dan tarbiyah, tidak mungkin bisa terbangun masyarakat Islami yang menjadi syarat bagi tegaknya syariat Islam dan berdirinya negara Islam].